Diversification in substrate usage by glutathione synthetases from soya bean (Glycine max), wheat (Triticum aestivum) and maize (Zea mays). - Skipsey, M; Davis, B; Edwards, R (2005)
Unlike animals which accumulate glutathione (gamma-glutamyl-L-cysteinyl-glycine) alone as their major thiol antioxidant, several crops synthesize alternative forms of glutathione by varying the carboxy residue. The molecular basis of this variation is not well understood, but the substrate specificity of the respective GSs (glutathione synthetases) has been implicated. To investigate their substrate tolerance, five GS-like cDNAs have been cloned from plants that can accumulate alternative forms of glutathione, notably soya bean [hGSH (homoglutathione or gamma-glutamyl-L-cysteinyl-beta-alanine)], wheat (hydroxymethylglutathione or gamma-glutamyl-L-cysteinyl-serine) and maize (gamma-Glu-Cys-Glu). The respective recombinant GSs were then assayed for the incorporation of differing C-termini into gamma-Glu-Cys. The soya bean enzyme primarily incorporated beta-alanine to form hGSH, whereas the GS enzymes from cereals preferentially catalysed the formation of glutathione. However, when assayed with other substrates, several GSs and one wheat enzyme in particular were able to synthesize a diverse range of glutathione variants by incorporating unusual C-terminal moieties including D-serine, non-natural amino acids and alpha-amino alcohols. Our results suggest that plant GSs are capable of producing a diverse range of glutathione homologues depending on the availability of the acyl acceptor.